Estrategias didácticas para el aprendizaje, en el área de matemática de los niños de séptimo grado de la escuela “Ing. Hermel Tayupanda” de San Jacinto de Culluctús, parroquia Sicalpa, cantón Colta, provincia de Chimborazo, año lectivo 2015–2016. - Guamán Pilco, Olga Delfina (2017)
From a historical perspective, mathematics has been the driving force of the human being. For this reason, it is considered a key area of individuals’ learning process. It actively involves the students in the construction of their own knowledge by applying motivational strategies to improve their academic performance. With the objective that the teaching-learning process is linked to the strategies, methods and instruments used by the teacher to take students from the seventh grade of the "Ing. Hermel Tayupanda “School at San Jacinto de Culluctús, parish of Sicalpa, Colta province of Chimborazo, in the academic year 2015 - 2016 to an effective and lasting learning in everyday coexistence. The theoretical base is the usage of different updated national and international texts. The research has a non-experimental design, descriptive, correlational, analytical, and documentary and field, because surveys were conducted in the place of the facts. Direct observation and survey were instrument of data collection and applied to a population of 19 students. From this research it is deduced that the application of new didactic strategies for teaching mathematics is a common concern among teachers, since in our country, whose central objective is to improve the quality of education and the goal is immerse the student as Basic unit and promoter of social change, it was concluded that the students are not very participative, they are not involved in the learning process, so that the teacher must investigate new didactic strategies and motivational abilities to teach mathematics in a practical and effective way.